2007
DOI: 10.1007/s11207-007-9034-2
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Transformation of a Flux Rope to an ICME

Abstract: Abstract. The solar wind conditions at one astronomical unit (AU) can be strongly disturbed by the interplanetary coronal mass ejections (ICMEs). A subset, called magnetic clouds (MCs), is formed by twisted flux ropes that transport an important amount of magnetic flux and helicity which is released in CMEs. At 1 AU from the Sun, the magnetic structure of MCs is generally modeled neglecting their expansion during the spacecraft crossing. However, in some cases, MCs present a significant expansion. We present h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
170
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 148 publications
(177 citation statements)
references
References 46 publications
7
170
0
Order By: Relevance
“…In some cases, both MCs even travel consecutively and the flux rope signatures are preserved . On the other hand, Dasso et al [2007] also considered whether the substructure could be explained by a small twisted flux tube with opposite helicity sign in the center of the flux rope and concluded that the formation of such a structure is not possible in the corona. It is, however, possible for two flux ropes with the same sign of helicity to interact in interplanetary space, but the symmetrical nature of the 13 April 2006 flux rope signature in B y,cloud implies that the flux ropes would have to be very similar to reproduce the observed substructure signatures, and it is very improbable that this is the case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, both MCs even travel consecutively and the flux rope signatures are preserved . On the other hand, Dasso et al [2007] also considered whether the substructure could be explained by a small twisted flux tube with opposite helicity sign in the center of the flux rope and concluded that the formation of such a structure is not possible in the corona. It is, however, possible for two flux ropes with the same sign of helicity to interact in interplanetary space, but the symmetrical nature of the 13 April 2006 flux rope signature in B y,cloud implies that the flux ropes would have to be very similar to reproduce the observed substructure signatures, and it is very improbable that this is the case.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Dasso et al [2007] also suggested the simplest interpretation of the observed substructure may be spatial oscillations of the magnetic field, introduced as a result of interactions between a magnetic cloud and the ambient solar wind as the cloud propagates into interplanetary space. They proposed that close to the minimum approach of the magnetic cloud center, the spacecraft trajectory would be nearly tangential to the magnetic flux surfaces of the flux rope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this effect can be corrected, and it is usually not the main cause of the observed asymmetry between the front and back of MCs . Moreover, even removing the aging effect, a front/back asymmetry can still be observed in some MCs Dasso et al 2007). Finally, we find that the deformation of the flux-rope core decreases with higher spatial frequency deformations of the boundary.…”
Section: Discussionmentioning
confidence: 99%
“…One significant difference is the inclusion or not of a region of strong magnetic field without much rotation at the "back" of the MC (until 02:40 on November 8). Previous studies (Dasso et al, 2006;Dasso et al, 2007;Möstl et al, 2008) have discussed how reconnection between a MC and the ambient solar wind during the ICME propagation may result in this type of regions which, actually, belong to the MC. Each researcher decided exactly where to end the MC.…”
Section: Event 27mentioning
confidence: 99%